أثر نظم المعلومات الضريبية المحوسبة على جودة الإقرارات الضريبية والأداء الضريبي من خلال الحوكمة الضريبية: الدور الملطف للتدين وافشاء المعلومات في دائرة ضريبة الدخل والمبيعات الاردنية - طارق سميح حسين هناند
As a result of the tremendous developments in information technology, there is a shortcoming in adopting the tax accounting used in the Income and Sales Tax Department. which still suffers from its lack of modern techniques in accounting, especially for linking and collecting tax from taxpayers, such as the electronic payment and tax collection system. This study aims to identify the impact of computerised tax information systems on the quality of income tax statements and tax performance in the Jordanian Income and Sales Tax Department. It also aims to identify the mediating role of tax governance as well as the moderating role of religiosity and disclosure of information. To achieve this, the analytical-descriptive approach was relied upon. Where the study population consisted of all Jordanian income and Sales Tax Department auditors ،a simple random sample was taken. Furthermore, 224 questionnaires were subjected to statistical analysis after deleting missing values and outliers. Additionally, 8 interviews were conducted with department managers and heads of audit departments. The results of SPSS and Smart PLS4 found that there is a positive and significant effect of computerised tax information systems on the quality of the income tax statement and tax performance. In addition, tax governance has a partial mediating effect between computerised tax information systems and the quality of the income tax statement and tax performance. There is also a positive and significant impact of the powers and privacy on the disclosure of information. which improves the relationship between computerised tax information systems and the quality of income tax statements and tax performance. Moreover, the findings indicate that religiosity has a moderate effect on the relationship between computerised tax information systems and the quality of the income tax statement and tax performance, as well as between information disclosure and the quality of the income tax statement. Furthermore, this study recommends that Jordanian Income and Sales Tax should develop and update the electronic system periodically. as well as working to link the Jordanian Income and Sales Tax Department with all sensitive government departments, such as the Land and Survey Department, banks, and the Ministry of Municipalities. which shows the extent of the credibility of the tax returns submitted by the taxpayer. This link contributes to ensuring the speedy completion of work and improving the efficiency of tax performance, starting with submitting a high-quality tax return that is compatible with records in other government departments.